A Pilot Study Testing the Efficacy of dCBT in Patients With Cancer Experiencing Sleep Problems - Chung, Kyong-Mee; Suh, Yung Jae; Chin, Siyung; Seo, Daesung; Yu, Eun-Seung; Lee, Hyun Jeong; Kim, Jong-Heun; Kim, Sang Wun; Koh, Su-Jin (Frontiers in Psychology, 2022)
Objective This pilot study aimed to evaluate the efficacy of a digital cognitive behavioral therapy (dCBT) in patients with cancer experiencing sleep problems. Methods A total of 57 participants aged 25–65 years (6M/51F with a mean of 42.80 years and a standard deviation of 14.15 years) were randomly assigned to three groups—21 participants to a dCBT program (HARUToday Sleep), 20 participants to an app-based attentional control program (HARUCard Sleep), and 16 participants to a waitlist control group—and evaluated offline before and after the program completion. Of the 57 participants, there were a total of 45 study completers, 15 participants in each group. The dependent variables were sleep quality scores, measured by the Pittsburgh Sleep Quality Index (PSQI) and health-related quality of life scores, measured using the Short-Form 36 (SF-36), and attentional bias scores from a dot-probe computer task. Results For both the intention-to-treat (N = 57) and study-completers analyses (N = 45, 15 for each group), a significant increase supported by a large effect size was found in the quality of sleep score of the HARUToday Sleep group compared to both the app-based attentional control and the waitlist control group. However, no significant changes were found in the quality of life and attentional bias scores. Conclusion Our results suggest that the HARUToday Sleep app has the potential to serve as an intervention module to enhance the sleep quality of patients with cancer experiencing sleep problems.